The Effectiveness of “Dialogic Reading Method” in Increasing Prosocial Behavior in Preschool Children - alifah indalika mulyadi razak (SEA-CECCEP, 2020)
This study aims to stimulate prosocial communication through active two-way communication in dialogic reading speech method. Prosocial behavior reflected in this study consisted of: (1) Helping; (2) Sharingand (3) Comforting. Prosocial behavior is important for children to be accepted and make friends. It supports the process of teaching and learning activities. One intervention that is considered effective in improving prosocial communication is through active two-way communication. This study involved preschool children (n = 100) spread across two early childhood institutions in Bandung Regency using the-before-after-experimental study method consisting of a control group and an experimental group. The result of this study showed that Dialogic reading effectiveness test in the experimental group through dialogic reading method had a significant influence on the prosocial behavior of preschool children (Asymp. Sig. (2-tailed) = 0 <α = 0.05).